2022
DOI: 10.3389/fcvm.2021.804934
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoregulation of Vascular Endothelial Growth Factor Receptor 2 in Angiogenesis

Abstract: The endothelial cells that compose the vascular system in the body display a wide range of mechanotransductive behaviors and responses to biomechanical stimuli, which act in concert to control overall blood vessel structure and function. Such mechanosensitive activities allow blood vessels to constrict, dilate, grow, or remodel as needed during development as well as normal physiological functions, and the same processes can be dysregulated in various disease states. Mechanotransduction represents cellular res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 266 publications
0
13
0
Order By: Relevance
“…The mechano-sensitivity of endothelial cells induces blood vessel constriction, dilation, growth, or remodeling, as needed during development and under normal physiological conditions. (15) Recently, it was suggested that impaired angiogenesis could contribute to increased peripheral resistance, which leads to increased blood pressure. (16,17) Essential hypertension is thought to be a consequence of structural and functional alterations in the growth of the microvascular network, due to abnormal regulation of angiogenesis.…”
mentioning
confidence: 99%
“…The mechano-sensitivity of endothelial cells induces blood vessel constriction, dilation, growth, or remodeling, as needed during development and under normal physiological conditions. (15) Recently, it was suggested that impaired angiogenesis could contribute to increased peripheral resistance, which leads to increased blood pressure. (16,17) Essential hypertension is thought to be a consequence of structural and functional alterations in the growth of the microvascular network, due to abnormal regulation of angiogenesis.…”
mentioning
confidence: 99%
“…Importantly, BDNF produced after resistance exercise has direct or indirect interaction with IGF-1, that is, it can help the brain increase IGF-1, promote nerve growth and produce serum angiotensin and amino acid, and then stimulate more BDNF receptors to increase the connection between neurons. This neurobiochemical mechanism can act on such central nervous system regions as the forebrain, striatum, hippocampus, cerebral cortex, spetum neurons, cerebellum, and motor neurons ( 98 ). These brain structures are all related to cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
“…We found that its expression in human pituitary tumors is approximately 2-fold that of normal pituitary tissue (FLT1 in Figure 1 ). VEGFR2 is expressed mostly in vascular endothelial cells ( 68 ). Both VEGFA and VEGFC bind to VEGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…Both VEGFA and VEGFC bind to VEGFR2. VEGFR2 is the predominant receptor mediating VEGF-induced vascular angiogenesis ( 29 , 68 ). Consistent with this, we found that VEGFR2 expression is more than 8-fold higher in pituitary tumors than in normal pituitary tissue (KDR in Figure 3A ).…”
Section: Discussionmentioning
confidence: 99%